Optimization of Purchase Decisions: A Segmentation, Targeting, and Positioning Approach at AMIU Malabo Depot - Hasan, Hamida; Putra, Pandi (Jurnal Manajemen Bisnis, 2024)
This study investigates how marketing strategies—specifically segmentation, targeting, and positioning—affect consumer decision-making when purchasing refill drinking water at AMIU Depot Malabo, Parepare. Utilizing a quantitative research approach, the study employs various data collection methods, including direct observation, conversations with respondents, distributing questionnaires, and reviewing documents. Participants were selected incidentally from consumers at AMIU Depot Malabo. The findings indicate that both segmentation and targeting have a significant effect on purchasing decisions, while positioning does not appear to have a substantial impact. However, when considered together, these three strategies significantly influence purchasing behavior. Additional analysis shows that the independent variables account for some variation in consumer purchasing decisions. To enhance understanding, it is recommended that future research explore other factors that might affect the decision-making process for refill drinking water consumers.